VARIATIONS OF FOLIAR CARBON ISOTOPE DISCRIMINATION AND NUTRIENT CONCENTRATIONS IN ARTEMISIA ORDOSICA AND CARAGANA KORSHINSKII AT THE SOUTHEASTERN MARGIN OF CHINA’S TENGGER DESERT - Zhao L.; Xiao H.; Liu X. (My University, 2006)
Seasonal variations in foliar stable carbon isotope discrimination (Δ) of Artemisia ordosica and Caragana korshinskii and correlations of foliar Δ with N, P, and K concentrations were studied under different planting regimes at the southeastern margin of China’s Tengger Desert. Foliar Δ, N, P, and K concentrations and the correlations of Δ with N, P, and K differed between the species and planting regimes. Foliar Δ, P and K concentrations in A. ordosica were markedly higher than in C. korshinskii, while foliar N concentrations in C. korshinskii was significantly higher than in A. ordosica. There were no significant differences in N, P, and K concentrations in C. korshinskii between planting regimes, but foliar Δ was significantly increased after June in mixed-species planting. In A. ordosica foliar N concentrations in mixed-species planting and foliar Δ in single-species planting were significantly higher than those of corresponding planting regimes. According to water-use efficiency (WUE) calculated based on foliar Δ, and on N, P, and K concentrations, C. korshinskii’s survival may profit from its higher WUE, whereas A. ordosica can avoid drought damage by its higher P and K concentrations in leaves in arid or semi-arid environments. The complex correlations of foliar Δ with foliar N, P and K suggested that water in C. korshinskii and water and P nutrition in A. ordosica were the key factors limiting their growth.
Keywords: STABLE CARBON ISOTOPE DISCRIMINATION (Δ); NUTRIENT CONCENTRATIONS; A. ORDOSICA; C. KORSHINSKII